Offensive activity as an element of the evaluation of struggle dynamics of judo contestants - Boguszewski, D. (Archives of Budo, 2014)
Background & Study Aim: Analyses of the actions taken at start by the contestants of combat sports deliver a considerable amount of valuable information for the training staff. Evaluation of technical and tactical preparation of judokas has recently been performed on the basis of various criteria. The purpose of this study was to propose a new element of measuring the combat dynamics of judokas - offensive activity (OA), and comparing it with currently functioning indexes. Material & Methods: The research has been executed on the basis of DVD records from 41 final combats from the most important worldwide judo championships, which took place between 2007 and 2010. 69 leading judokas of the world, representing 27 countries, took part in the championships. The analyses were performed on the basis of the Kalina`s method of combat dynamics measurement. The combat dynamics phenomenon is defined by the following indexes: activeness, effectiveness of attack, effectiveness of counterattacks and defensive effectiveness. A new element was proposed as an addition - offensive activeness, as a counterpart of the combat dynamics evaluation. Result: The activeness of contestants did not exceed 0.5, which means that, for over a half of their combats, judokas did not take any actions (neither offensive nor defensive). The winners of final combats were characterized by much higher offensive activeness, effectiveness of attack and defensive activeness. The analysis of events in the time function indicated that the highest combat effectiveness was recorded in the fourth minute of the combat, and the lowest - in the first minute. Conclusion: The offensive activeness index may be very helpful in analyzing both the actions of contestants and the referees (particularly in the case of equalizers or draws).